2019
DOI: 10.1002/jcb.29055
|View full text |Cite
|
Sign up to set email alerts
|

circPIP5K1A serves as a competitive endogenous RNA contributing to ovarian cancer progression via regulation of miR‐661/IGFBP5 signaling

Abstract: Increasing evidence demonstrates the crucial regulatory functions of circular RNAs in different cancer types. The major aim of the current study was to establish functions of circPIP5K1A during ovarian cancer. Our results showed an increased expression of circPIP5K1A in both ovarian cancers and cell lines, which was associated with poor prognosis. In functional analyses, downregulation of circPIP5K1A suppressed ovarian cancer cell migration, proliferation, and invasion in vitro. The miR-661 was indicated as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 32 publications
0
33
0
Order By: Relevance
“…However, studies support that IGFBPs can exert either an oncogenic or an onco-suppressive role, via the regulation of the IGFR/MAPK and IGFR/PI3K/AKT signaling pathways [ 77 ]. It has been observed that circRNAs increase the levels of specific oncogenic IGFBPs, and, subsequently, promote cancer progression [ 78 , 79 ]. However, whether cancer progression is mediated through IGFR/MAPK and/or IGFR/PI3K/AKT signaling activation remains to be revealed.…”
Section: Circrna-mediated Regulation Of Major Signaling Pathwaysmentioning
confidence: 99%
“…However, studies support that IGFBPs can exert either an oncogenic or an onco-suppressive role, via the regulation of the IGFR/MAPK and IGFR/PI3K/AKT signaling pathways [ 77 ]. It has been observed that circRNAs increase the levels of specific oncogenic IGFBPs, and, subsequently, promote cancer progression [ 78 , 79 ]. However, whether cancer progression is mediated through IGFR/MAPK and/or IGFR/PI3K/AKT signaling activation remains to be revealed.…”
Section: Circrna-mediated Regulation Of Major Signaling Pathwaysmentioning
confidence: 99%
“…Recent data have proved that several circRNAs can influence the growth, survival, invasion, EMT, angiogenesis, and drug resistance in gynecological cancers. Manipulation of circRNA abundance has been shown to possess anti-tumor activities in experimental xenograft models of CC [88,91,95], OC [121,123,124] and EC [156].…”
Section: Circrnas As Potential Therapeutic Targets For Gynecological mentioning
confidence: 99%
“…Several circRNAs (such as circEPSTI1, circGFRA1, circ0051240, circPIP5K1A, circPVT1 and circABCB10) have been found to increase the proliferative and invasive capacities of OC cells by acting as miRNA sponges [ 121 , 122 , 123 , 124 , 125 , 126 ]. Knockdown of circSMAD7 by short-hairpin RNA (shRNA) was associated with decreased cell proliferation, migration and invasion and with increased expression of KLF6 in CC cells [ 127 ].…”
Section: The Expression Functions and Mechanisms Of Circrnas In Gmentioning
confidence: 99%
“…CircRNAs, a new class of ncRNAs with the special ring structure, are stably expressed in multiple cells and once considered as transcriptional splicing intermediates, byproducts or accidental splicing errors. Accumulating evidences indicated that circRNAs play a key regulatory role in cell physiological process and human diseases, including cancer via sponging miRNAs or interacting with various proteins [190][191][192]. In addition, the annular structure endows circRNAs with inherent stability, which enables them to accumulate in exosomes and exist stably in peripheral body fluids such as plasma and saliva.…”
Section: Circrnas and Chemoresistance In Gastric Cancermentioning
confidence: 99%